Research and practice of Internet traffic regulating strategy based on big data acquisition and analysis of flow - MA Yunying; WANG Shenghuan (Dianxin kexue)
With the development of China’s digital economy, Internet traffic has shown a steady growth trend. In view of the problem that the uneven distribution of Internet traffic will affect the long-term stable development of the network, the methods of Internet traffic acquisition and identification were discussed. The network architecture for traffic collection, and the software architecture for traffic analysis were constructed. A feasible market-oriented strategy for regulating and channeling Internet traffic was proposed. The propoced strategy has achieved preliminary results through the practice of operators, and it provides a solution and reference basis to guide the distribution of Internet traffic in a proper way.